2014
DOI: 10.1002/hep.27322
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional changes of serum albumin: Clinical and prognostic significance in hospitalized patients with cirrhosis

Abstract: Beside the regulation of fluid distribution, human serum albumin (HSA) carries other activities, such as binding, transport, and detoxification of many molecules. In patients with cirrhosis, HSA exhibits posttranscriptional alterations that likely affect its functions. This study aimed at identifying the structural HSA alterations occurring in cirrhosis and determining their relationship with specific clinical complications and patient survival. One hundred sixty-eight patients with cirrhosis, 35 with stable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
129
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 30 publications
9
129
0
9
Order By: Relevance
“…Several studies have shown that posttranscriptional structural and subsequent functional alterations might occur in the structure of albumin due to several factors and new isoforms arise (21,22). These changes are minimal under physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that posttranscriptional structural and subsequent functional alterations might occur in the structure of albumin due to several factors and new isoforms arise (21,22). These changes are minimal under physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic liver diseases, in addition to the decreased synthesis of albumin by the liver, concentrations of different albumin isoforms also increase due to alteration of the microenvironment within the liver or effects of several prooxidants. Some of these albumin isoforms were shown to be related to ascites, renal dysfunction, and bacterial infections in patients with chronic liver diseases (21). On the other hand, it was shown that serum concentration of naturally protected native albumin was much lower than total serum albumin concentration in cirrhotic patients and more importantly this undamaged native albumin concentration was found to be related to survival in patients with chronic liver diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…28) Similarly, Jalan et al found that the 1-year survival rate for liver cirrhosis patients could be predicted by the concentration of reduced HSA in their plasma. 29) Taking into consideration the fact that modified albumin molecules lack multiple functions, Domenicali et al proposed that the concentration of reduced HSA should be measured to indicate the "effective albumin concentration" as a new indicator in lieu of the conventional parameter total albumin concentration. 29) In the present study, the concentration of reduced HSA was not decreased with the administration of the ferric citrate formulation; therefore, there was no reduction in the effective albumin concentrations (from 1.92±0.22 to 2.09±0.27 (g/dL)), suggesting that the administration of the ferric citrate formulation is unlikely to increase the risk of cardiovascular disease via the induction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to quantitative changes, HA undergoes structural and functional alterations that are probably favoured by the pro-inflammatory and pro-oxidant state of advanced cirrhosis 6,7 . Extensive post-transcriptional changes, involving several sites of the molecule, develop and increase in parallel with the disease severity 7 . Physiological functions of HA appear to be impaired, including the ability to chelate cobalt and binding and transport capacities 8 .…”
Section: -Lowmentioning
confidence: 99%
“…Physiological functions of HA appear to be impaired, including the ability to chelate cobalt and binding and transport capacities 8 . It can, therefore, be hypothesised that, in patients with cirrhosis, the global function of HA, resulting from both oncotic and non-oncotic properties, is not only related to its absolute concentration in the circulation, but also to the degree of preservation of its structural and functional integrity [5][6][7][8] . Advanced cirrhosis is characterised by two major systemic features: circulatory dysfunction and chronic inflammation.…”
Section: -Lowmentioning
confidence: 99%